2015
DOI: 10.1080/1573062x.2015.1036761
|View full text |Cite
|
Sign up to set email alerts
|

Increasing green roof plant drought tolerance through substrate modification and the use of water retention gels

Abstract: The optimal provision of green roof services is largely dependent on the health of the vegetation on the green roof, which is often affected by water availability.We assessed the impact of two substrate components, brick particle size and a polyacrylamide gel additive, and a living mulch (companion planting of Sedum spp.) on the growth, physiological and visual health of newly established plugs of Festuca ovina and Linaria vulgaris during an extreme drought (25 days) in a controlled environment greenhouse. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…According to it, fillings of plants modules presented plenty of solid growing medium, such as gravel, expanded clay, shingle, growstones, pumice, rock wool, perlite, vermiculite, coconut fiber, rice husks, thatch, straw, sand, or the like. In study [4] the impact of two substrate components assessed: brick particle size and a polyacrylamide gel additive, living mulch on the growth, physiological and visual health of newly established green rooftops during 25 days of extreme drought, and this study shows that coarser particle size substrates can significantly improve the drought tolerance of plants on green roof.…”
Section: Key Benefits Of Green Roof Systemsmentioning
confidence: 78%
“…According to it, fillings of plants modules presented plenty of solid growing medium, such as gravel, expanded clay, shingle, growstones, pumice, rock wool, perlite, vermiculite, coconut fiber, rice husks, thatch, straw, sand, or the like. In study [4] the impact of two substrate components assessed: brick particle size and a polyacrylamide gel additive, living mulch on the growth, physiological and visual health of newly established green rooftops during 25 days of extreme drought, and this study shows that coarser particle size substrates can significantly improve the drought tolerance of plants on green roof.…”
Section: Key Benefits Of Green Roof Systemsmentioning
confidence: 78%
“…Soil physical and chemical properties could be improved by different soil amendments [37][38][39][40]. Water retention capacity and available water content could be greatly improved by organic manures [37], organic waste recycled in agriculture [38], Zeolites [39], the use of different types of biochar [40][41][42], or synthetic hydrogels [43,44]. Constructed green roofs with a deeper substrate layer could also retain more water and reduce runoff volume [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Bates et al (2015) found plant recovery from drought was facilitated by media characteristics, with media high in crushed brick performing the best from a group of recycled aggregate materials tested. Additives for increasing the water holding capacity of media such as polyacrylamide gel have been shown to significantly increase plant recovery following a drought period (Young et al, 2015), while others have shown biologically based additives such as seaweed hold promise to improve both water and nutrient holding capacity of greenroof media (Vijayaraghavan and Joshi, 2015). integrating greenroofs with other stormwater practices (e.g., rainwater harvesting and landscape irrigation) to reduce potential impacts of nutrient export.…”
Section: Field Laboratory and Modeling Hydrologicmentioning
confidence: 99%